2014
DOI: 10.3748/wjg.v20.i8.2098
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cell markers correlate with early recurrence and survival in hepatocellular carcinoma

Abstract: Expression of CD133, CD90, and EpCAM CSC markers may be linked to HCC tumor onset and/or progression. In addition, EpCAM expression is associated with shorter survival time, while CD90 expression is associated with early HCC recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
76
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 0 publications
4
76
1
2
Order By: Relevance
“…20,21 The prognosis of patients with EpCAM-negative HCC is considered to be better than that of those with EpCAM-positive HCC. 11,[14][15][16]20,21 Although EpCAM expression was not found to be an independent predictor of survival in patients with HCC in this study, EpCAM expression was found to be associated with well-known unfavorable prognostic factors in HCC. Thus, the use of EpCAM expression as an unfavorable prognostic factor of HCC is reasonable.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…20,21 The prognosis of patients with EpCAM-negative HCC is considered to be better than that of those with EpCAM-positive HCC. 11,[14][15][16]20,21 Although EpCAM expression was not found to be an independent predictor of survival in patients with HCC in this study, EpCAM expression was found to be associated with well-known unfavorable prognostic factors in HCC. Thus, the use of EpCAM expression as an unfavorable prognostic factor of HCC is reasonable.…”
Section: Discussionmentioning
confidence: 63%
“…15,21 The proportion of tissues expressing EpCAM in this study was a little higher than in earlier series, which reported EpCAM in 15.9%-48.7% of HCCs. [15][16][17][20][21][22][23] have demonstrated that EpCAM expression was observed more often in HCC patients with HBV than in those with other etiologies, and the immunoreactivity of EpCAM has been found in up to 78% of HCC patients with HBV. The high proportion of HCC patients with HBV (74%) examined in this study might be a possible explanation for the higher EpCAMpositive rate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations